Anthelmintic Effects of the Essential Oil of Fennel (Foeniculum vulgareMill., Apiaceae) against Schistosoma mansoni. Issue 7 (July 2015) - Wakabayashi, Kamila A. L.; de Melo, Nathalya I.; Aguiar, Daniela P.; de Oliveira, Pollyanna F.; Groppo, Milton; da Silva Filho, Ademar A.; Rodrigues, Vanderlei; Cunha, Wilson R.; Tavares, Denise C.; Magalhães, Lizandra G.; Crotti, Antônio E. M.
Abstract Foeniculum vulgare Mill. (Apiaceae), known as fennel, is a widespread aromatic herbaceous plant, and its essential oil is used as additive in the food, pharmaceutical, cosmetic, and perfume industries. The in vitro antischistosomal activity and cytotoxic effects against V79 cells of the essential oil of F. vulgare cultivated in southeastern Brazil (FV‐EO) was investigated. The FV‐EO was obtained by hydrodistillation and characterized by GC‐FID and GC/MS analyses. (E)‐Anethole (69.8%) and limonene (22.5%) were identified as the major constituents. Its anthelmintic activity against Schistosoma mansoni was evaluated at concentrations of 10, 50, and 100 μg/ml, and it was found to be active against adult S. mansoni worms, although it was less effective than the positive control praziquantel (PZQ) in terms of separation of the coupled pairs, mortality, and decreased motor activity. However, FV‐EO elicited an interesting dose‐dependent reduction in the number of S. mansoni eggs. On their own, (E)‐anethole and the limonene enantiomers were much less effective than FV‐EO and PZQ. An XTT‐cytotoxicity‐based assay evidenced no FV‐EO cytotoxicity against V79 cells. In summary, FV‐EO displayed moderate in vitro schistosomicidal activity against adult S. mansoni worms, exerted remarkable inhibitory effects on the egg development, and was of low toxicity.